Enhancing Collaborative Learning in Information Systems Business Analytics Using Data Visualisation and Manipulation Techniques : Final Report. - Cybulski, Jacob; Marjanovic, Olivera; Mather, Dineli; Keller, Susan; Saundage, Dilal; Dharmasena, Lasitha; Munro, Judy (Office for Learning and Teaching, 2016)
Business analytics refers to skills, methods and technologies that enable managers to make swift, quality decisions based on large amounts of data generated and collected by their organisations. Given the pressures of modern management practice, business analytics has become the foundation for management and information systems courses despite the inherent complexity of its curriculum. It is slowly moving into the early years of the business curriculum, where low numeracy skills and the fundamental lack of business knowledge impede student learning of abstract concepts. This problem was addressed by structuring learning tasks to take advantage of students' general world-knowledge, their intuitive approach to problem solving, preference for learning by experimentation and their eagerness to share personal experiences with peers. This project developed a visual business analytics collaboratory -a web-based facility, shared and maintained by the two partner universities, and open to community learners, where 3D visualisation techniques and immersive interfaces would allow intuitive learning of business analytics.